Integration of the L3 Learning Environment into the WiBA-Net Project - Tripathi, Arun Kumar; Rößling, Guido; Trnková, Jana; Tillack, Karin (Proceedings of the International Conference on Networked Learning, 2002)
WiBA-Net aims to provide a multimedia network platform for the civil engineering and architecture students in different German and Austrian universities. WiBA-Net shall provide a flexible learning atmosphere, in which learners can easily access materials according to their way of learning. Learning can be independent of time and space. The learner can also exchange information with other learners. WiBA-Net is an interdisciplinary project in which several German and Austrian universities are collaborating. Currently, 31 educators provide content for the WiBA-Net, coming from universities in Germany , Austria , Switzerland , Denmark and Hungary . At the Darmstadt University of Technology, the Telecooperation Research Group, Civil Engineering department and the research group on education and technology at the institute for Pedagogy are collaborating.